Identification of the endogenous cysteine-rich peptide trissin, a ligand for an orphan G protein-coupled receptor in Drosophila. - Ida, T.; Takahashi, T.; Tominaga, H.; Sato, T.; Kume, K.; Yoshizawa-Kumagaye, K.; Nishio, H.; Kato, J.; Murakami, N.; Miyazato, M.; Kangawa, K.; Kojima, M. (Biochemical and Biophysical Research Communications, 2011)
There are many orphan G protein-coupled receptors (GPCRs), for which ligands have not yet been identified, in both vertebrates and invertebrates, such as Drosophila melanogaster. Identification of their cognate ligands is critical for understanding the function and regulation of such GPCRs. Indeed, the discovery of bioactive peptides that bind GPCRs has enhanced our understanding of mechanisms underlying many physiological processes. Here, we identified an endogenous ligand of the Drosophila orphan GPCR, CG34381. The purified ligand is a peptide comprised of 28 amino acids with three intrachain disulfide bonds. The preprotein is coded for by gene CG14871. We designated the cysteine-rich peptide "trissin" (it means for triple S-S bonds) and characterized the structure of intrachain disulfide bonds formation in a synthetic trissin peptide. Because the expression of trissin and its receptor is reported to predominantly localize to the brain and thoracicoabdominal ganglion, trissin is expected to behave as a neuropeptide. The discovery of trissin provides an important lead to aid our understanding of cysteine-rich peptides and their functional interaction with GPCRs.